Upaya Peningkatan Motivasi Dan Hasil Belajar Biologi Melalui Model Pembelajaran Cooperative Script Siswa Sma Negeri 1 Lahusa Tahun Pelajaran 2024/2025 - Festina Lase; Jun Mardin Telaumbanua (GEN BIONIX: Jurnal Ilmiah Pendidikan Biologi, 2025)
Low learning motivation is often the root of the problem of suboptimal student learning outcomes, a condition also found in SMA Negeri 1 Lahusa. This study aims to describe the improvement of learning quality, motivation, and learning outcomes in Biology through the application of the Cooperative Script learning model. Using a Classroom Action Research (CAR) design, this research was conducted in two cycles on 29 students of Class XI-MIPA-3. Data were collected through observation sheets, questionnaires, learning achievement tests, and interviews, then analyzed quantitatively descriptively. The findings showed a significant increase in all observed variables. In Cycle I, learning quality and learning motivation only reached 64.70% and 67.31% respectively with the "sufficient" category, with an average learning outcome of 71.90. Dramatically, Cycle II showed a progressive leap; learning quality increased to 98.55% and learning motivation to 95.31%, both in the "very good" category, followed by an increase in the average learning outcome to 82.93. These results prove that the implementation of the Cooperative Script model is effectively able to create improvements in the learning process which have direct implications for increasing student motivation and academic achievement.